Variation im europäischen Kontrast. Untersuchungen zum Satzanfang im Deutschen, Französischen, Norwegischen, Polnischen und Ungarischen - Schwinn, Horst (Konvergenz und Divergenz. Sprachvergleichende Studien zum Deutschen, 2016)
This volume presents the findings of a European research network on the comparative description of German. The key area of exploration was corpus-assisted comparative research on grammatical variations in the left sentence periphery. The compendium provides insight into topological and information structural aspects of German in comparison to the French, Norwegian, Polish, and Hungarian languages.